Optimum sizing of GCPV system under tropical condition - Ab Rahman, Azhan; Mohd Zambri, Mohd Khairi; Wan Mohd Kamil, Wan Nur Syahirah; Ramli, Mohd Zulkifli; Bohari, Zul Hasrizal (University of El Oued, 2018)
Solar panel and photovoltaic (PV) inverter are the two elements that cost the most in a Grid-Connected Photovoltaic (GCPV) system installation. This research hence aims to determine the optimum sizing ratio between the two for the practice in the tropical climate condition. To do so, five minute average of year 2014 profile of tilted irradiance and back panel temperature data were gathered to be used in testing process. Testing was done by simulating the GCPV system by using DC simulator at three different sizing ratios: 1 to 1, 1 to 0.8 and 1 to 1.2by referring to the ratio between solar panel and inverter. Experimental results showed that the optimum sizing ratio is 1:0.8. This is because, at this setting, the simulation produced the highest system efficiency and the maximum value of system yield. In addition, this setting can also reduce the initial cost of GCPV system installation.